Raziskovanje v javni RR sferi in inženirstvo - Vodopivec, Franc (Kovine zlitine tehnologije, 1998)
Causes for the critically low share of applied and development research backed by public funding are analysed. Several measures are proposed for increasing the extent and the efficiency of the state funded technical and technological research and for a greater role of engineering.
Keywords: raziskovanje; technology; tehnologija; inženirstvo; kvaliteta; učinkovitost; efficiency; politics; politika